Desenvolvimento e caracterização de blendas e de compostos empregando polímeros biodegradáveis - Casarin, Suzan Aline (2004)
This work presents theoretical information and experimental data on the behavior of biodegradable polymers and blends of biodegradable PHB polymer with copolyesters that are also biodegradable. Binary mixtures were made of the biodegradable polymer poly(hydroxybutyrate) PHB and biodegradable copolyesters, Eastar Bio® and Ecoflex®, in the following PHB/copolyester compositions: 100/0, 90/10, 75/25, 50/50, and 0/100. For the PHB/copolyester blend of 75/25, modifications with 30% of wood powder in two different grain sizes were studied. The polymeric blends were prepared and their mechanical and thermal properties and morphology evaluated. An analysis of their biodegradation in soil was also made. It was found that the mechanical properties of PHB polymer are improved by incorporating 50% of copolyester into the polymeric blend. Analyses of the melt flow index also revealed that the three polymers studied here are unstable and degrade along time, a behavior displayed particularly strongly by Easter Bio. A thermal analysis by Differential Scanning Calorimetry indicated that these polymers have a very slow crystallization rate. A Dynamic Mechanical Thermal Analysis of the blends indicated they are immiscible, as indicated by two different Tg peaks very close to the Tg of the pure polymers. All the polymers subjected to the soil biodegradation tests underwent degradation with a loss in mass, although only superficial alterations which did not interfere in their mechanical properties occurred during the 90-day evaluation period.